Autistic Regression Sequelae or Relapse for NMDA Receptor Antibody Encephalitis. (5th December 2022) - Zaid, Ghaida Khalaf; Saini, Chetan; Awais, Khadija; Shah, Namrata S
Abstract : Objective: To highlight a pediatric presentation of autistic regression secondary to relapsing NMDA receptor antibody encephalitis (NMDARAE) post-HSV infection. Background: It is reported that 30% of patients develop NMDA receptor antibodies (NMDARA) after HSV Encephalitis. Previous studies have demonstrated a significant association between prior HSV-1 infection and NMDARAE, a diagnosis often overlooked due to diverse neurological manifestations. Design/Methods: NA. Results: This case highlights a 5-year-old female presenting with fever and refractory status epilepticus, was diagnosed with HSV Encephalitis requiring prolonged hospitalization. At discharge she had insomnia, mutism, dyskinetic movements, atonic seizures, and developmental regression. At 3 months post-discharge EEG exhibited multiple generalized myoclonic, myoclonic tonic, and atonic seizures, MRI brain demonstrated right temporal lobe encephalomalacia with immunologic workup demonstrating positive serum and CSF NMDARA. She underwent treatment with intravenous steroids followed by plasmapheresis and then rituximab with an improved clinical response and seizure control at 6 months. At 9 months, she displayed behavioral changes with diagnosis of ADHD with autistic regression. Workup was positive for NMDARA in the CSF (18 months post-presentation) and EEG showed diffuse epileptiform discharges activated during sleep. She was treated with steroids followed by rituximab. At follow-up, she showed improved social interaction, sleep, and seizure control with persistence of some autistic and ADHD features. Conclusions: About 90% of patients with NMDARE present with prominent behavioral manifestations, with challenges in differentiating from psychiatric diseases. Relapse is reported in 12-24% of cases and is associated with delayed treatment and the female gender. NMDARAE relapse post-HSV Encephalitis is underreported, especially cases demonstrating autistic regression, as in our case. In conclusion, given overlapping and subtle symptoms, it is crucial to recognize the varying presentations and early diagnosis of NMDARAE relapse for effective treatment and better outcome.